School Climate, Moral Disengagement and, Empathy as Predictors of Bullying in Adolescents - Montero-Carretero, Carlos; Pastor, Diego; Santos-Rosa, Francisco Javier; Cervelló, Eduardo (Frontiers in Psychology, 2021)
Our work aimed to study the relationships between different dimensions of school climate, moral disengagement, empathy, and bullying behaviors (perpetration and victimization). The study sample consisted of 629 students (304 boys and 325 girls) aged 12 to 14 years (M =12.55, SD =.67). Results showed how different dimensions of school climate predicted moral disengagement, empathy, and victimization, and these, in turn, predicted bullying perpetration. The results show the need to generate favorable educational environments to reduce the levels of moral disengagement and victimization and to increase empathy in students as a strategy to prevent negative consequences related to bullying.